INDICATORS OF BUSINESS ZAKAT AMONGST SMALL BUSINESS: CONCEPT AND CONTEMPORARY NEEDS - Safruddin Halimiy Kamaluddin; Uba Rezeki Harahap; M. Wildan Ali Japar Nasution (UIN Imam Bonjol Padang, 2022)
This paper describes the continuing Zakat and its benefits in contemporary times. People give Zakat as Allah's right to those who are entitled to receive, among others, the poor, according to the provisions of the Islamic religion. Zakat is an Amaliyah practice that has a significant effect on poverty alleviation. The author conducted a literature study and descriptive analysis approach to get Zakat with terms and conditions to create social justice and balance in growing Muslim communities and Muslims' economies. Developing productive Zakat with Islamic law calculations will revive the ummah economy and significantly help the economic growth rate. Islam supports the rotation of the economy of the ummah. In Islam, it is recommended that the assets continue to rotate so as not to be eaten up by Zakat; the greater the amount of productive Zakat, the smaller the percentage to be paid is like Zakat on livestock. Not only that, the flexibility of Islamic law can be an option for economic development by the situation and conditions at hand. Because the madhab's opinion is incorrect, every ijtihad is Zani (relative to its truth). Therefore, Zakat can be used along with the rules according to the situation and conditions. It is hoped that the turnover of zakat assets in productive inflammation can increase the Nisab of Zakat, which interacts with the community's economic growth. This productive Zakat will support the family's food security, providing capital to increase agricultural output in food production centers.